Is Needle Aspiration for Peritonsillar Abscess Still as Good as We Think? A Long-term Follow-up. (April 2015) - Shaul, Chanan; Koslowsky, Benjamin; Rodriguez, Mercedes; Schwarz, Yehuda; Muahnna, Nidal; Peleg, Uri; Sichel, Jean-Yves
Objective: The aim was to study the therapeutic management, recurrence, and need for tonsillectomy in patients who underwent needle aspiration for peritonsillar abscess (PTA). Methods: A prospective observational design study was performed. Patients hospitalized in Shaare Zedek Medical Center between the years 2004 and 2007 with a diagnosis of PTA who underwent needle aspiration obtaining pus were included. A minimum 5-year follow-up was required for all patients. Recurrences, complications, the need for a repeated surgical procedure, length of hospital admission, and tonsillectomy were the primary end points. Results: The study included 117 patients. One hundred four patients (88.9%) improved after 1 needle aspiration without any other intervention, whereas 13 patients (11.1%) required an additional procedure. Broad spectrum antibiotics showed a statistical advantage over penicillin only, regarding need for recurrent procedure (14.7% vs 4.7%, P = .02). No short- or long-term complications were documented. Seventeen patients (14.5%) had any recurrence. Primary recurrent tonsillitis, female sex, and younger age were predictive risk factors for recurrent events of PTA (32% vs 10%, P < .01). A total of 18 patients (15.4%) eventually underwent tonsillectomy. Conclusion: Needle aspiration is an effective first line procedure for patients with PTA. Tonsillectomy is not necessary in most cases. In our study, young age, female sex, and recurrent tonsillitis are negative prognostic factors for recurrence. These patients should be managed accordingly. Broad spectrum antibiotics may offer additional advantages when compared to penicillin only.